"Print‐to‐pattern": Silk‐Based Water Lithography. Issue 47 (12th September 2018) - Liu, Zhen; Zhou, Zhitao; Zhang, Shaoqing; Sun, Long; Shi, Zhifeng; Mao, Ying; Liu, Keyin; Tao, Tiger H.
Abstract: The requirement of nontoxic and versatile manufacturing frameworks for biologically relevant applications has imposed significant constraints on the choice of functional materials and the complementary fabrication tools. In this context, silk is actively studied, thanks to its mechanical robustness, biocompatibility, wide availability, aqueous processing conditions, and ease of functionalization. The inherent matching between the water solubility of silk and the aqueous inks of the inkjet printing (IJP) process has derived a biofriendly and versatile "print‐to‐pattern" scheme—termed silk‐based water lithography—toward scalable functional biomanufacturing. The deposition mode of IJP and the etching effect of silk film by water features a dual tone fabrication where functional molecules are dispensed additively, while the silk film is patterned in a "subtractive" fashion. Such versatility and scalability pave the way to a wide range of opportunities in the biomedical field. Abstract : A silk‐based water lithography technique is reported. The inherent matching between the water solubility of silk and the aqueous inks of inkjet printing process derives a biofriendly and versatile "print‐to‐pattern" scheme—termed silk‐based water lithography—toward scalable functional biomanufacturing (less than 0.01 s per 4" wafer with 2048 nozzles in the current setup).